Numerical analysis of ship motion under linear and nonlinear waves - Armudi, Amanda; Marques, Wiliam Correa; Oleinik, Phelype Haron (Scientia Plena, 2017)
Simulating physical phenomena by applying mathematical and numerical modeling has been increasingly used during the different stages of research and development and innovation projects. The purpose of this study is to present results about translational motion (x, y, z), angular motion (α, β, γ) and trajectories obtained using a numerical model developed to study ship dynamics under the influence of linear and nonlinear waves. The results indicated that translational motion, surge and sway, is mostly influenced by thrust in the studied scenario. The translational motion (heave) displayed curves which can be related with wave patterns before 0.1 hr. The angular motion distributions displayed a variation that can be related with wave forces. However, at 0.4 hr the curves depicted smaller variations that is explained by the increased engine thrust pattern. In both simulations, the distance of 20.582 km and 20.342 km for linear and nonlinear simulations were calculated, respectively. Once both simulations yielded similar values for travel distance, the wave patterns used in this study were shown to generate variations at the displacement from 0 to 0.4 hr. After 0.4 hr, the ship displacement depicted linear curves but the engine thrust was able to overcome the external forces.